Experimental validation of a target method for balancing exhaust ventilation duct systems with dampers. - Dodrill M; Guffey SE (Journal of Occupational & Environmental Hygiene, 2008)
This study tested the 'Target Method' for adjusting ventilation systems. The Target Method is based on target hood static pressures (SPhtarget) computed in a manner designed to take into account the estimated effects of dampers on the fan, the order of damper adjustments, and the ratio of the prebalancing branch airflows to their goals. It is aimed at achieving a desired relative distribution of airflows even if the fan output is far from ideal. The method assumes the fan output will be adjusted after the dampers are adjusted. The method is expected to produce lower fan pressure requirements than some commonly used methods. The method was tested on a working seven-branch, full-sized exhaust ventilation system in the West Virginia University Exposure Assessment Laboratory. Two radically different target distributions were tested with two replications apiece. Both target distributions of airflows were substantially different from the initial distribution, providing a high degree of challenge to the methodology. For each distribution, SPhtarget values were computed for the first round of adjustments. Each damper was adjusted until the observed value of the hood static pressure was nearly equal to that damper's computed SPhtarget value for that distribution. Each of the other branch dampers was adjusted similarly in turn. After the first round of adjustments, the median ratio of SPh to SPhtarget provided the targets for the partial second round of adjustments. Twenty-point Pitot traverses were used to determine the airflow in each branch duct both before and after employing the adjustment method, providing the basis to determine the success in reaching each of the two desired distributions. The percentage of excess airflow (assuming ideal adjustment of the fan speed) was below 2.2% for all experimental trials. An unpublished study by Vivek Balasubramanian showed that excess airflow was 4.8% to 8.5% in the same experimental system after two full rounds of adjustment using the customary Target Method. Under poor measurement conditions, the greater uncertainty of pressure measurements would likely produce somewhat higher excess airflows.